Deletion of the Mycobacterium tuberculosis cyp138 gene leads to changes in membrane-related lipid composition and antibiotic susceptibility - Lu, Yun; Chen, Hongtong; Shao, Zhiyuan; Sun, Lang; Li, Congran; Lu, Yu; You, Xuefu; Yang, Xinyi (Frontiers in Microbiology, 2024)
Mycobacterium tuberculosis (Mtb), the main cause of tuberculosis (TB), has brought a great burden to the world's public health. With the widespread of Mtb drug-resistant strains, the pressure on anti-TB treatment is increasing. Anti-TB drugs with novel structures and targets are urgently needed. Previous studies have revealed a series of CYPs with important roles in the survival and metabolism of Mtb. However, there is little research on the structure and function of CYP138. To discover the function and targetability of CYP138, in our study, a cyp138-knockout strain was built, and the function of CYP138 was speculated by the comparison between cyp138-knockout and wild-type strains through growth curves, growth status under different carbon sources, infection curves, SEM, MIC tests, quantitative proteomics, and lipidomics. The knock-out of cyp138 was proved to affect the Mtb's macrophage infection, antibiotics susceptibility, as well as the levels of fatty acid metabolism, membrane-related proteins, and lipids such as triacylglycerol. We proposed that CYP138 plays an important role in the synthesis and decomposition of lipids related to the cell membrane structure, as a new potential anti-tuberculosis drug target.